Gene Expression Signatures of Porcine Bone Marrow-Derived Antigen-Presenting Cells Infected with Classical Swine Fever Virus - Liani Coronado; Miaomiao Wang; Jose Alejandro Bohórquez; Adriana Muñoz-Aguilera; Mònica Alberch; Patricia Martínez; Nicolas Ruggli; Yuliaxis Ramayo-Caldas; Llilianne Ganges (Viruses)
For a better understanding of classical swine fever (CSF) pathogenesis, a transcriptomic analysis was performed using porcine bone marrow (BM)-derived antigen-presenting cells (APCs) infected ex vivo with two different cDNA-derived classical swine fever virus (CSFV) strains, the low-virulence Pinar de Rio (vPdR-36U) or the lethal vPdR-H30K-5U. The transcriptomic profile of vPdR-36U- or vPdR-H30K-5U-infected versus noninfected cells revealed 946 and 2643 differentially expressed genes (DEGs), respectively. The upregulation of ISG15, CXCL-10, ADAM8, and CSF1 was found after infection with vPdR-36U, which could contribute to the generation of mild CSF forms. In contrast, cells infected with the lethal vPdR-H30K-5U overexpressed the immune checkpoint molecules PD-L1, CD276, and LAG3, which are involved in T-cell exhaustion and could be associated with adaptive immunity impairment. vPdR-H30K-5U also induced increased expression of PPBP, IL-8, IL-6, ECE1, and Rab27b, which are mediators of inflammatory responses that can be involved in cytokine storms. The TNF signaling pathway, which is related to the activation and proliferation of different subsets of immune cells, including CD4+ T cells, was notably upregulated in response to the low-pathogenicity virus. The Th17, Th1, and Th2 differentiation pathways were downregulated by the highly pathogenic virus only, supporting the role of T-cell-mediated immunity in protecting against CSFV.